Star Wars. Episode IX, The rise of Skywalker [videorecording (Blu-Ray)] - Abrams, J. J. (Jeffrey Jacob), 1966-; Fisher, Carrie; Hamill, Mark; Driver, Adam; Ridley, Daisy, 1992-; Boyega, John; Isaac, Oscar; Daniels, Anthony; Nyong'o, Lupita; Russell, Keri, 1976-; Williams, Billy Dee, 1937- (Disney Blu-ray., 2020)
When it's discovered that the evil Emperor Palpatine did not die at the hands of Darth Vader, the rebels must race against the clock to find out his whereabouts. Finn and Poe lead the Resistance to put a stop to the First Order's plans to form a new Empire, while Rey anticipates her inevitable confrontation with Kylo Ren.